Regulating Electrocatalytic Oxygen Reduction Activity of a Metal Coordination Polymer via d–π Conjugation. Issue 31 (26th June 2021) - Ni, Youxuan; Lin, Liu; Shang, Yuxin; Luo, Lin; Wang, Liubin; Lu, Yong; Li, Yixin; Yan, Zhenhua; Zhang, Kai; Cheng, Fangyi; Chen, Jun
Abstract: Non‐noble transition metal complexes have attracted growing interest as efficient electrocatalysts for oxygen reduction reaction (ORR) while their activities still lack rational and effective regulation. Herein, we propose a d–π conjugation strategy for rough and fine tuning of ORR activity of TM‐BTA (TM=Mn/Fe/Co/Ni/Cu, BTA=1, 2, 4, 5‐benzenetetramine) coordination polymers. By first‐principle calculations, we elucidate that the strong d–π conjugation elevates the d xz /d yz orbitals of TM centers to enhance intermediate adsorption and strengthens the electronic modulation effect from substitute groups on ligands. Based on this strategy, Co‐TABQ (tetramino benzoquinone) is found to approach the top of ORR activity volcano. The synthesized Co‐TABQ with atomically distributed Co on carbon nanotubes exhibits a half‐wave potential of 0.85 V and a specific current of 127 mA mgmetal −1 at 0.8 V, outperforming the benchmark Pt/C. The high activity, low peroxide yield, and considerable durability of Co‐BTA and Co‐TABQ promise their application in oxygen electrocatalysis. This study provides mechanistic insight into the rational design of transition metal complex catalysts. Abstract : A two‐step strategy was proposed to optimize the ORR activity of TM‐BTA (TM=Mn/Fe/Co/Ni/Cu, BTA=1, 2, 4, 5‐benzenetetramine) analogs by screening preliminarily TM centers and subsequently substituent groups. Strong d–π conjugation in TM‐BTA is found to elevate the d xz /d yz orbitals, which enhances the activity of TM centers, and also enlarges the impact of ligand functional groups on d orbitals of TM centers.